Pengaruh Diversitas Gender dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Sektor properties dan Real Estate yang Terdaftar di BEI tahun 2022-2024 (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines the influence of gender diversity and company size on the sustainability of the financial performance of companies in the property and real estate sector listed on the IDX in the 2022-2024 period. This research employed a quantitative approach using panel data regression analysis. The population consisted of all property and real estate companies listed on the Indonesia Stock Exchange, with the sampling technique using a census method. A total of 35 companies were selected, resulting in 105 observations. Secondary data were collected through documentation techniques using annual financial reports obtained from the official website of the Indonesia Stock Exchange and each company’s website. The findings indicate that partially, gender diversity has a negative but insignificant effect on financial performance, while firm size has a positive but insignificant effect on financial performance. Simultaneously, gender diversity and firm size influence financial performance. These findings emphasize the importance of corporate governance structures and company characteristics in supporting corporate financial performance. This study is limited to property and real estate companies during the 2022–2024 period. Future research is recommended to include additional variables and broader research objects.